Translating evidence for low back pain management into a consumer-focussed resource for use in community pharmacies: a cluster-randomised controlled trial. - Helen Slater (Public Library of Science (PLoS), 2013)
Background This cluster-randomised controlled trial determined the effectiveness of an evidence-based, pamphlet intervention in improving low back pain (LBP)-related beliefs among pharmacy consumers. Methods THIRTY FIVE COMMUNITY PHARMACIES WERE RANDOMISED TO THREE GROUPS: pamphlet+education intervention [n = 11]; pamphlet only intervention [n = 11]; control: usual care [n = 13]. Eligibility requirements for clusters included: community-based pharmacies and proprietor participation consent. Pharmacy consumers (N = 317) aged 18-65 years currently experiencing LBP participated. Intervention group allocation depended on the pharmacy attended. Individual-level outcomes were measured at pre-intervention (T0), at two (T1) and eight (T2) weeks post-intervention and included beliefs about LBP [Back Pain Beliefs Questionnaire (BBQ); Fear Avoidance Beliefs Questionnaire (FABQ)]. Secondary outcomes included pain severity, activity impairment and pamphlet perceived usefulness. Blinding to group allocation included primary investigators, outcome assessors and the statistician. Pharmacy staff and consumers were un-blinded. Results Of 35 pharmacies recruited (317 consumers), no clusters were lost to follow-up. Follow-up was available for n = 24 at 2 weeks only; n = 38 at 8 weeks only; n = 148 at both time points, with n = 148+24+38 = 210 analysed (107 excluded: no follow up). Adjusting for baseline scores demonstrated no significant differences in beliefs (2 or at 8 weeks) between pamphlet (with or without education) versus control, or between 'pamphlet with' versus 'without' education. Work-related fear (FABQ) was significantly lower in consumers receiving pamphlet (with or without education) versus control (difference -2.3, 95%CI: -4.4 to -0.2). There was no significant difference between "pamphlet with" versus "pamphlet without" groups. Consumers receiving the "pamphlet with" reported greater perceived usefulness than consumers receiving the "pamphlet without" (difference 0.9 (95%CI: 0.0 to 1.8)). Conclusion Community pharmacies provided a feasible primary care portal for implementing evidence-based information. The associated improvement in work-related LBP-beliefs for consumers receiving the pamphlet suggests this simple intervention may be a useful component of care. Trial registration ACTR.org.au ACTRN12611000053921.